Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/eurheartj/suz042
|View full text |Cite
|
Sign up to set email alerts
|

Angina and chronic obstructive pulmonary disease: facing the perfect storm

Abstract: The association of chronic obstructive pulmonary disease (COPD) and ischaemic heart disease (IHD) is challenging both in terms of prognosis and of pharmacological treatment. An 83-year-old Caucasian male patient has chronic kidney disease, COPD, previous myocardial infarction, coronary artery bypass graft with left internal mammary artery (LIMA) on left anterior descending (LAD), saphenous vein graft (SVG) on obtuse marginal (OM)1 and on right coronary artery, and percutaneous coronary intervention (PCI) on LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“…Importantly, we observed that, after adjustment to various factors, ATE value decreased from 8.4% in model 1 to 5.0% in model 2, demonstrating the observed differences in the estimates due to adjustment with lifestyle and morbidity factors. COPD and coronary artery disease are highly prevalent chronic conditions; both conditions share common risk factors 33 , 50 . COPD is characterized by progressive airflow limitation due to chronic airway inflammation 50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, we observed that, after adjustment to various factors, ATE value decreased from 8.4% in model 1 to 5.0% in model 2, demonstrating the observed differences in the estimates due to adjustment with lifestyle and morbidity factors. COPD and coronary artery disease are highly prevalent chronic conditions; both conditions share common risk factors 33 , 50 . COPD is characterized by progressive airflow limitation due to chronic airway inflammation 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The association between COPD and Ischemic Heart Disease (IHD) exerts adverse consequences on overall prognosis. The development of both COPD and IHD is attributed to several shared factors, including exposure to inhaled noxious particles, hypoxia, systemic inflammation, endothelial dysfunction, heightened platelet reactivity, and increased arterial stiffness 33 , 34 , 34 , 35 , 35 . Notably, cardiovascular-related mortality in a significant portion of these patients follows shortly after an acute exacerbation of COPD 33 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often necessary to distinguish AECOPD from acute heart failure and coronary heart disease in clinical research. At the same time of treatment and management, it is necessary to treat both situations in many aspects, such as medication and rehabilitation (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…The patients with established CAD and COPD had more severe atherosclerosis vs those without COPD [55]. Another study showed that patients with COPD had more atherosclerotic lesions found in PCI compared with patients without COPD, and these patients had a higher mortality rate [56,57].…”
Section: Features Of the Course Of Hypertension Coronary Artery Disea...mentioning
confidence: 99%